2003
DOI: 10.1002/cm.10137
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the transition from vimentin to neurofilaments during neuronal differentiation

Abstract: Vimentin (Vm) is initially expressed by nearly all neuronal precursors in vivo, and is replaced by neurofilaments (NFs) shortly after the immature neurons become post-mitotic. Both Vm and NFs can be transiently detected within the same neurite, and Vm is essential for neuritogenesis at least in culture. How neurons effect the orderly transition from expression of Vm as their predominant intermediate filament to NFs remains unclear. We examined this phenomenon within growing axonal neurites of NB2a/d1 cells. Tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 60 publications
4
45
0
Order By: Relevance
“…The identification of interlinked peptides between various domains of NFM and VIME suggests that extensive interaction interfaces exist between these two proteins and potentially implicate VIME involvement in the polymerization or regulation of neurofilament proteins in HEK 293 cells. It has been reported that VIME co-localizes with neurofilament proteins dynamically during neuronal differentiation, and its co-purification with NFH and NFL has been observed (49). Given the close relationship among the three neurofilament subunits NFL, NFM, and NFH, our findings corroborate well with the known function of vimentin in the development of neurofilaments.…”
Section: Identification Of Azide-a-dsbso Cross-linked Peptides Via Lc-mssupporting
confidence: 88%
“…The identification of interlinked peptides between various domains of NFM and VIME suggests that extensive interaction interfaces exist between these two proteins and potentially implicate VIME involvement in the polymerization or regulation of neurofilament proteins in HEK 293 cells. It has been reported that VIME co-localizes with neurofilament proteins dynamically during neuronal differentiation, and its co-purification with NFH and NFL has been observed (49). Given the close relationship among the three neurofilament subunits NFL, NFM, and NFH, our findings corroborate well with the known function of vimentin in the development of neurofilaments.…”
Section: Identification Of Azide-a-dsbso Cross-linked Peptides Via Lc-mssupporting
confidence: 88%
“…2 A, B) and in Triton X-100-insoluble fractions ( Fig. 2 L), consistent with a filamentous assembly in Neuro2a cells (Yabe et al, 2003). GFP-tagged NF-L protein expressed from transgenes lacking NF-L 3ЈUTR (pGFP/NFϪ3ЈUTR) does not colocalize with endogenous NF-H but is diffusely distributed throughout the perikarya and neurites at low and high levels of transgene expression ( Fig.…”
Section: Nf-l 3utr Promotes Colocalization Of Nf-l Protein With Endogsupporting
confidence: 66%
“…Cytoskeletons were prepared from sciatic nerve of adult FVB mice of both genders constitutively expressing green fluorescent protein (GFP)-tagged NF-H (Letournel et al, 2006), NB2a/d1 cells constitutively expressing GFP-tagged NF-M (Yabe et al, 2003;Yabe et al, 2001a) or murine spinal cord (which were labelled with rhodamine after harvesting as described below). Cytoskeletons were prepared by sedimentation of homogenates of the above tissues and cells at 15,000 g for 15 minutes in 50 mM Tris (pH 6.8) containing 5 mM EDTA, 1 mM phenylmethanesulphonylfluoride (PMSF) and 50 μg/ml leupeptin as described (Yabe et al, 2001a).…”
Section: Cytoskeletal Preparationsmentioning
confidence: 99%